Noninvasive diagnosis of urothelial cancer in urine using DNA hypermethylation signatures—Gender matters. Issue 10 (16th May 2019) - Köhler, Christina U.; Bonberg, Nadine; Ahrens, Maike; Behrens, Thomas; Hovanec, Jan; Eisenacher, Martin; Noldus, Joachim; Deix, Thomas; Braun, Katharina; Gohlke, Henning; Walter, Michael; Tannapfel, Andrea; et al.
Abstract : Urothelial cancer (UCa) is the most predominant cancer of the urinary tract and noninvasive diagnosis using hypermethylation signatures in urinary cells is promising. Here, we assess gender differences in a newly identified set of methylation biomarkers. UCa‐associated hypermethylated sites were identified in urine of a male screening cohort ( n = 24) applying Infinium‐450K‐methylation arrays and verified in two separate mixed‐gender study groups ( n = 617 in total) using mass spectrometry as an independent technique. Additionally, tissue samples ( n = 56) of mixed‐gender UCa and urological controls (UCt) were analyzed. The hypermethylation signature of UCa in urine was specific and sensitive across all stages and grades of UCa and independent on hematuria. Individual CpG sensitivities reached up to 81.3% at 95% specificity. Albeit similar methylation differences in tissue of both genders, differences were less pronounced in urine from women, most likely due to the frequent presence of squamous epithelial cells and leukocytes. Increased repression of methylation levels was observed at leukocyte counts ≥500/μl urine which was apparent in 30% of female and 7% of male UCa cases, further confirming the significance of the relative amounts of cancerous and noncancerous cells in urine. Our study shows that gender difference is a most relevant issue when evaluating the performance of urinary biomarkers in cancer diagnostics. In case of UCa, the clinical benefits of methylation signatures to male patients may outweigh those in females due to the general composition of women's urine. Accordingly, these markers offer a diagnostic option specifically in males to decrease the number of invasive cystoscopies. Abstract : What's new? DNA hypermethylation signatures detected in exfoliated cells in urine may provide valuable information for the non‐invasive diagnosis of urothelial cancer (UCa). Here, the authors describe a newly identified urinary hypermethylation biomarker signature that is effective in diagnosing UCa. The hypermethylation signature was specific across UCa stage and grade and was independent of hematuria. The signature, however, was less pronounced in women compared to men. Women's urine had a higher prevalence of leukocytes and additional non‐cancerous epithelial cells, potentially rendering urinary hypermethylation signatures less applicable in female patients, an observation that is vitally important for clinical practice.